Kvorum na zakonodajnem referendumu v našem in v primerjalnem pravu - Žuber, Bruna (Pravnik, 2014)
The regulation of legislative referendum in constitutional systems of different European countries with a well developed direct democracy vary in three main points i.e. type and form of a referendum, procedures regarding its use and acceptance, and conditions required to accept the referendum decision. In theory, the conditions required to accept a referendum decision are classified into three groups. The first group of conditions relates to the majority required to accept the decision on the legislative referendum. The second group of conditions to accept the referendum decision are conditions regarding the quorums, i.e. the quorum of participation and the quorum of approval and rejection. The third group of conditions relates to other conditions required to accept the decision on the legislative referendum. The last ones are typical only of different referendum regulations in each individual country.Determining the quorum and other conditions to accept the referendum decision is facultative as opposed to the referendum majority and its purpose is mainly a greater legitimacy of the decision. In countries with a suspensive confirmative referendum the majority of voters who voted (relative majority) is needed to approve the law. In most cases, the quorum of participation and the quorum of approval are not provided. In countries with a suspensive rejective referendum the majority of voters as well as the quorum of rejection are required for the referendum decision to be accepted. In countries with an abrogative legislative referendum the quorum of participation is in most cases the condition to accept the referendum decision.The regulation of legislative referendum was a subject of constant criticism in Slovenia not so long ago. The regulations regarding the subjects that can initiate a referendum, the questions decided upon and the legitimacy of the referendum decision were among the most problematic issues. Constitutional Act amending Articles 90, 97 and 99 of the Constitution of the Republic of Slovenia changed the regulation completely. Consequently, the conditions required to accept the referendum decision were changed and strengthened.
Keywords: kvorum; referendum; udeležba